Land Cover Impacts on Land‐Atmosphere Coupling Strength in Climate Simulations With WRF Over Europe. Issue 18 (21st September 2020) - Jach, Lisa; Warrach‐Sagi, Kirsten; Ingwersen, Joachim; Kaas, Eigil; Wulfmeyer, Volker
Abstract: Land use and land cover changes are important human forcings to the Earth's climate. This study examines the land‐atmosphere coupling strength and the relationship between surface fluxes and clouds and precipitation for three land cover scenarios in the European summer. The WRF model was used to simulate one scenario with extreme afforestation, one with extreme deforestation, and one with realistic land cover for the time period between 1986 and 2015. The simulations were forced with ERA‐Interim reanalysis data. The analysis followed a two‐step approach. First, the convective triggering potential–low‐level humidity index framework was applied to locate potential coupling hot spots, which were then analyzed with regard to their sensitivity toward land use and land cover changes. Second, actual feedbacks between evaporative fraction, cloud cover, and precipitation were analyzed statistically with focus on sign and location of the feedbacks. The results demonstrate that coupling hot spots, exhibiting predominantly positive feedbacks, were identified over parts of Eastern Europe and Scandinavia. In this strongly coupled region, afforestation and deforestation modified the atmospheric humidity and stability by changing the surface flux partitioning. Afforestation is associated with a net drying of the atmosphere due to a disproportionately strong increase in the sensible heat flux. In contrast, deforestation initiated a moistening of the atmosphere. The total precipitation changed only in limited areas significantly, which are mostly located in mountainous regions and the northeast of the domain. In summary, the results indicate a land surface influence on the atmospheric background conditions, and an impact on the potential strength of land surface‐precipitation feedbacks. Key Points: A region of strong coupling was identified in the northeast of Europe, and the location was not shifted by land use and land cover changes Land‐atmosphere feedbacks appear to be mainly positive in Europe, and extreme afforestation and deforestation modify the coupling strength Significant impacts on clouds and precipitation occur over mountains and the coupling hot spot; however, the impacts are rather limited